The Potential of Indonesian Natural Materials as Immunomodulators and Tonics for National Resilience of Public Health in the Era Covid-19 Pandemic - Timbul Partogi Haposan Simorangkir; Syahrul Tuba; Reynatha Chrestella Amandara Pangsibidan (Budapest International Research and Critics University, 2022)
Indonesia is abundant in natural substances with immunomodulatory and tonic qualities that can help maintain immunity and keep the body healthy in the face of the COVID-19 pandemic. This paper Analysing herbal plants that are effective in terms of safety and actual efficacy in increasing the endurance and fitness of Indonesians in the face of the Covid 19 Pandemic becomes the first step in pioneering efforts to create national drug independence and sovereignty in the context of national health sector resilience. This study suggests that herbal plants such as Papaya (Carica papaya), Turmeric/Curcumin (Curcuma domestica), Meniran (Phyllanthus niruri), Brotowali (Tinospora crispa), and Ginger (Zingiber officinale Rosc.) which have immunomodulatory and tonic properties, as well as data on the potential for increasing endurance and body wellness by enhancing immune response, to raise awareness of the nation's ability and potential natural resources in supporting national drug independence, resilience, and sovereignty. Therefore, the usage of immunomodulator herbal medications is thought to have an activity to boost the immune system and protect the body from COVID-19 and preparedness for the next pandemic. However, these findings should be confirmed through additional scientific research or clinical trials.